THE EUROPEAN CONVENTION ON BIOMEDICINE AND HUMAN RIGHTS: A PRAGMATIC AMBITION - BYK, Christian (MEDECINE LEGALE DROIT MEDICAL, 2025)
What the European Convention on Biomedicine and Human Rights declares is very clear. While “bearing in mind (among others) the Universal Declaration of Human Rights proclaimed by the General Assembly of the United Nations on 10 December 1948 (and…) the Convention for the Protection of Human Rights and Fundamental Freedoms of 4 November 1950”, it also proclaims that man is “conscious of the accelerating developments in biology and medicine”. Therefore, it establishes a duality of time between the Human Rights principles, which are universal, and developments in biology and medicine which are dependent on the course of time and its acceleration. Experience is part of this race of time and this is experience which guided the elaboration of the European Convention on Biomedicine and Human Rights and this guidance involved two steps. The first one concerned the experience acquired by the Council of Europe in the field of medical and health ethics while the second one attempted to harmonize legislations in the area of reproductive technologies and human genetics. However, moving from step one to step two revealed a great change in the approach of ethics, outing it from the medical community to incorporate it into a public debate related to Human Rights and social transformations.